2011
DOI: 10.4314/ajdas.v9i2.64140
|View full text |Cite
|
Sign up to set email alerts
|

Gender, locus of control and smoking habits of undergraduate students

Abstract: Health psychologists believe that a significant proportion of human morbidity and mortality could be significantly reduced and humans' quality of life greatly enhanced if people could be helped to correct their health-impairing habits and behaviours, such as smoking and other forms of substance abuse. The present study investigated the influence of gender and locus of control on smoking habit of 230 smoking student-patrons of two relaxation centers in Ago-Iwoye, the host community of Olabisi Onabanjo Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The importance of HLC as a predictor of the smoking of conventional cigarettes among the general population and adolescents has been reported earlier by many authors [21][22][23][24][25][26][27]29]. Usually, they confirmed that higher CHLC was related to the higher likelihood of smoking.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The importance of HLC as a predictor of the smoking of conventional cigarettes among the general population and adolescents has been reported earlier by many authors [21][22][23][24][25][26][27]29]. Usually, they confirmed that higher CHLC was related to the higher likelihood of smoking.…”
Section: Discussionsupporting
confidence: 61%
“…Eiser et al observed, among a large group of school students 11-16 years old, that smokers, compared to non-smokers, showed lower OHLC and IHLC and higher belief in the importance of a "chance" influence on their health outcomes [25]. Many more recent studies confirmed a significant association between external HLC and smoking habits among youths and young adults [26][27][28][29]. Unfortunately, the relationship between HLC and the proclivity towards the use of e-cigarettes has not been reported on yet.…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy scale 95 Unidimensional Situational confidence questionnaire 96 8 -(5 Intrapersonal factors) negative emotional states, testing personal control, urges and temptations, positive emotional states, negative physical states + (3 interpersonal factors) interpersonal conflict, social pressure to drink and positive emotional states Drinking self-efficacy questionnaire 97 3 -Social pressure, opportunistic drinking and emotional relief Relapse situation efficacy questionnaire 98 7 -Negative affect, positive affect, restrictive situations, idle time, social/food, low arousal and craving Drinking refusal self-efficacy questionnaire revised 99 3 -Opportunistic drinking, social pressure and emotional relief Alcohol abstinence self-efficacy 100 4-Negative affect, social aspect, physical aspect and withdrawal and urges Confidence inventory revised 101 3 -Social aspect, negative/affective and habit/addictive Refusal skills scale 102 Not reported Confidence questionnaire 103 7 -Restlessness, intrapersonal negative mood states, crutch, time structuring, social, interpersonal negative mood states, self-image Self-regulation Self-regulation questionnaire 104,105 7 -Receiving relevant information, evaluating the information and comparing it to norms, triggering change, searching for options, formulating a plan, implementing the plan, assessing the plan's effectiveness Self-regulation inventory 106 5 -Positive action, controllability, expression of feelings and needs, assertiveness and well-being seeking Volition Volition components inventory 107 3 -Self-regulation, self-control, volitional inhibition 65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80 Exploring voluntariness as captured through FW…”
Section: Constructmentioning
confidence: 99%
“…Hence, early use of tobacco increases the likelihood of contracting non-communicable diseases and greater chances of morbidity and mortality. [20] Other health problems associated with tobacco use and dependence include the development of cardiovascular diseases, [21,22] chronic obstructive pulmonary disease, many forms of cancer (e.g., lung, trachea, and bronchus cancers), [20,[23][24][25][26] as well as major disabling conditions, such as dementia, blindness (macular degeneration), deafness, peripheral vascular disease (leading to amputations), stroke, and premature death, [11] and therefore presents a major public health concern.…”
Section: Introductionmentioning
confidence: 99%